Pengaruh Kualitas Pelayanan Jasa Perbankan Terhadap Loyalitas Nasabah Bank BJB Pada Kantor Cabang Pembantu Ujung Berung - Itto Turyandi (KarismaPro, 2019)
Emulation in the existing banking world is very tightening, and with condition of market where consumer or in this case is client has some banking service choices which will be applied, this thing will make transfer of client becomes increasingly as usual out of one banks to bank the other. For the purpose is required hard work in maintaining client loyality, one of its way is by giving quality of banking service activities as good as possibly. Bank Jabar Banten (Bank BJB) be an bank institute owned by the Government of West Java and Banten which now becomes bank having scale national. In facing emulation in this banking world always does improvement of quality of banking service activities, peculiarly from tangible, empathy, reliability, responsiveness, until quality of service activities passed to client.This research aim to study influence quality of banking service activities to client loyality at Bank BJB assistant office of branch Ujung Berung. Variable involved in by this research consisted of independent variable that is quality of banking service activities (X) and its the dependent variables is client loyality (Y). Method applied is survey where information from respondent is collected direct inly place of case systematically, as a mean to knows and forecasts some behaviour aspects from the population. As for research type done is descriptive and verifikatif.Result of this research known that contribution joinly client loyality to quality of banking service activities from result of coefficient of determination has influence equal to 74.8% and 25.2% influenced by other factor of which is not discussed in this research. As for sub-variabel pawn quality of banking service activities has biggest influence to client loyality, and sub-variabel direct proof has smallest influence to client loyality. Based on result of research as a whole, inferential that quality of banking service activities of influential positive and strong to client loyality Bank BJB assistant office of branch Ujung Berung. This thing is because of client in general feels quality of banking service activities given Bank BJB have been maximum and good.